Global optimization of batch and steady-state recycling chromatography based on the equilibrium model - Dienstbier, Jana; Schmölder, Johannes; Burlacu, Robert; Liers, Frauke; Kaspereit, Malte (Computers & Chemical Engineering, 2020)
An approach is presented for the optimal design of batch and steady-state recycling (SSR) chromatography. The optimization problem is decomposed into two stages. At the first stage, an efficient formulation as mixed-integer problem (MIP) is applied to obtain optimal fractionation times for chromatograms simulated by the equilibrium model. At the second stage, the optima are evaluated against a parametrized objective function. The chosen combination of model and optimization method provides a computationally very efficient tool. A comprehensive example study demonstrates that batch chromatography achieves the highest productivities at the cost of limited yields, which is optimal only for negligible feed costs. In other instances, the more flexible SSR concept provides larger profits. The results reveal also new optimal operating policies for SSR processes with segmented product fractions and waste streams.<br
Keywords: chromatography; steady-state recycling; global optimisation; mixed-integer programming; cost function

Multidimensional Fractionation of Particles - Frank, Uwe; Dienstbier, Jana; Tischer, Florentin; Wawra, Simon; Gromotka, Lukas; Walter, Johannes; Liers-Bergmann, Frauke; Peukert, Wolfgang (Separations, 2023)
The increasing complexity in particle science and technology requires the ability to deal with multidimensional property distributions. We present the theoretical background for multidimensional fractionations by transferring the concepts known from one dimensional to higher dimensional separations. Particles in fluids are separated by acting forces or velocities, which are commonly induces by external fields, e.g., gravitational, centrifugal or electro-magnetic fields. In addition, short-range force fields induced by particle interactions can be employed for fractionation. In this special case, nanoparticle chromatography is a recent example. The framework for handling and characterizing multidimensional separation processes acting on multidimensional particle size distributions is presented. Illustrative examples for technical realizations are given for shape-selective separation in a hydrocyclone and for density-selective separation in a disc separator.
Keywords: multidimensional separation; two-dimensional property distribution; size; shape; composition

Quality Control in Particle Precipitation via Robust Optimization - Kuchlbauer, Martina; Dienstbier, Jana; Muneer, Adeel; Hedges, Hanna; Stingl, Michael; Liers, Frauke; Pflug, Lukas (Computers & Chemical Engineering, 2024)

Robust Optimization in Nanoparticle Technology: A Proof of Principle by Quantum Dot Growth in a Residence Time Reactor - Dienstbier, Jana; Aigner, Kevin-Martin; Rolfes, Jan; Peukert, Wolfgang; Segets, Doris; Pflug, Lukas; Liers, Frauke (Computers & Chemical Engineering, 2021)
Knowledge-based determination of the best-possible experimental setups for nanoparticle design is highly challenging. Additionally, such processes are accompanied by noticeable uncertainties. Therefore, protection against these uncertainties is needed. Robust optimization helps determining such best possible processes. The latter guarantees quality requirements regardless of how the uncertainties, e.g. with regard to variations in raw materials, heat and mass transport characteristics, material properties and (growth) rates, manifest within predefined ranges. To approach this huge task, in this paper we exemplarily model a particle synthesis process with seeded growth by population balance equations and study different growth kinetics. We determine the mean residence time maximizing the product mass subject to a guaranteed yield. Additionally, we hedge against uncertain growth rates and derive an algorithmically tractable reformulation for the robustified problem. We evaluate our approach for seeded growth synthesis of zinc oxide quantum dots and demonstrate computationally that a guaranteed yield is met for all growth rates within previously defined regions. The protection against uncertainties only reduces the maximum amount of product that can be obtained by a negligible margin.<br
Keywords: particle design; robust optimization; process optimization; reformulation